THE IMPACT OF ENVIRONMENTAL CONSCIOUSNESS, ENVIRONMENTAL ATTITUDE AND PERCEIVED QUALITY OF GREEN PRODUCTS ON GREEN CONSUMER BEHAVIOUR OF MILLENNIALS IN NCT OF DELHI (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Climate change is now a problem of present  generation rather than future. In the present era,  the resolution of environmental issues should  be on the top priorities of all stakeholders  of society and efforts should be made to  minimize it as much as possible. Delhi is  10th most polluted city of the world and  it is facing more environmental problems.  Consumers are playing a significant role in  society and the over-consumption and over utilisation of the natural resources has led  to deterioration of nature (Chen & Chai,  2010). Consumers of millennial generations  are more sensitive to sustainability (Kapferer  & Michaut-Denizeau, 2020). This Paper  emphasis on Green Consumer Behaviour of  millennials and the impact of Environmental  Consciousness, Environmental Attitude and  Perceived Quality of green products on Green Consumer Behaviour of Millennials in NCT  of Delhi. A structured questionnaire has been  used to record the responses of 230 millennials  consumers of NCT of Delhi and SEM  technique is used to analyse the significance  of all the constructs used in the study. The  factors influencing Consumer Behaviour used  in various models is considered as the basic  idea for study in the light of Green Consumer  Behaviour and especially for millennials of NCT  of Delhi. The results found that all the factors  used in the study have a significant impact on  Green Consumer Behaviour. This paper has  mentioned the implications for marketers to  support the sustainable development of society.
Keywords: Environmental Consciousness; Green Consumer Behavior; Millennials